Neural Injury and Repair in a Novel Neonatal Mouse Model of Listeria Monocytogenes Meningoencephalitis. Issue 9 (6th September 2021) - Seele, Jana; Ballüer, Melissa; Tauber, Simone C; Bunkowski, Stephanie; Schulz, Katja; Stadelmann, Christine; Beineke, Andreas; Pägelow, Dennis; Fulde, Marcus; Nau, Roland
Abstract: To improve the therapy of neonatal central nervous system infections, well-characterized animal models are urgently needed. The present study analyzes neuropathological alterations with particular focus on neural injury and repair in brains of neonatal mice with Listeria monocytogenes (LM) meningitis/meningoencephalitis using a novel nasal infection model. The hippocampal formation and frontal cortex of 14 neonatal mice with LM meningitis/meningoencephalitis and 14 uninfected controls were analyzed by histology, immunohistochemistry, and in situ tailing for morphological alterations. In the dentate gyrus of the hippocampal formation of mice with LM meningitis/meningoencephalitis, an increased density of apoptotic neurons visualized by in situ tailing (p = 0.04) and in situ tailing plus immunohistochemistry for activated Caspase-3 (p < 0.0001) was found. A decreased density of dividing cells stained with an anti-PCNA-antibody (p < 0.0001) and less neurogenesis visualized by anti-calretinin (p < 0.0001) and anti-calbindin (p = 0.01) antibodies were detected compared to uninfected controls. The density of microglia was higher in LM meningitis (p < 0.0001), while the density of astrocytes remained unchanged. Infiltrating monocytes and neutrophilic granulocytes likely contributed to tissue damage. In conclusion, in the brains of LM-infected mice a strong immune response was observed which led to neuronal apoptosis and an impaired neural regeneration. This model appears very suitable to study therapies against long-term sequelae of neonatal LM meningitis.